Automated viper 150 low cost basic test station - Chee, Vincent Weng Keong. (2009)
CONNER Peripherals is a leading supplier of streaming tape drives and disk drives for computing systems. Competition, market volatility and evolving technologies require products that are manufactured to be both reliable and affordable. This paper describes the work involved to design a cost effective automated test system for an existing model of a tape drive product. It explains the steps needed to design the test system with minimum changes to the current product for testability and the considerations taken to design the cost effective automated test system. Product testability included the modification of existing circuitry, addition of new circuitry and firmware changes that were done such that the product can be tested automatically.